Distance education at the Algerian university in light of the Corona Covid-19 pandemic: between the requirements for establishing the right to education and facing obstacles - Djendli, Warda (Journal of Human Sciences, 2022)
With the emergence of the technological revolution and the spread of the Corona virus Covid-19, Algerian universities, like other universities in the world, have tended to integrate modern technologies into the educational process and digitize them With the aim of containing the virus on the one hand, and ensuring that the right to education is enshrined on the other hand and ensuring the continuation of education on the other hand by shifting from urban education to distance education The latter depends on technological methods and means, and needs a combination of material and human components in order to successfully activate this type of education and enable Algerian educational institutions to face the challenges and obstacles that hinder the quality of higher education from a distance.